Living Al-Qur'an dalam Ruang Politik: Melacak Resepsi Ayat Al-Qur'an dalam Bendera Pusaka Jayakarta Perspektif Semiotika - Alif, Muhtarul (SUHUF, 2023)
This article aims to trace the tradition of incorporating verses from the Koran into political symbols. The Living Al-Qur’an study studies how the Koran influences and is influenced by people’s understanding. However, there is rarely any study of the Living Al-Qur’an in the political sphere, even though the political sphere is a very large force in influencing the masses. The Jayakarta Heritage Flag is a symbol of the resistance of the Indonesian people which contains verses from the Koran. This research will reveal what the meaning of the internalization of the verse was, how the verse responded and was responded to by society at that time, and explain the importance of the values of the Koran in social life. The method used in this article is a qualitative method with the semiotic approach of C.S. Pierce. This is because each flag has a meaning and philosophy that is believed by its users. The object of observation in this research is the Jayakarta heritage flag with reference support from various literatures. The results of this study are that the Jayakarta Heritage Flag has nine sections that characterize Islamic values. Surah al-Ikhlas reflects monotheism, Surah al-An'am/6: 103 strengthens belief, Basmalah asks for blessings, Surah as-Saff/61: 13 as a spirit booster. The results of this research are expected to provide a new perspective in the study of the Living Al-Qur’an and to find out the values that inspire people’s struggles.